   Chapter 12.4, Problem 48E

Chapter
Section
Textbook Problem

# If a + b + c = 0. show thata × b = b × c = c × a

To determine

To show: The expression a×b=b×c=c×a .

Explanation

Given:

a+b+c=0 (1)

Rearrange the equation (1).

b=(a+c)

Consider a×b .

Substitute (a+c) for b ,

a×b=a×[(a+c)]=[a×(a+c)]=(a×a+a×c)=(0+a×c) {a×a=0}

Simplify the equation.

a×b=(a×c)

a×b=c×a (2)

Similarly, rearrange the equation (1).

a=(b+c)

Consider c×a

### Still sussing out bartleby?

Check out a sample textbook solution.

See a sample solution

#### The Solution to Your Study Problems

Bartleby provides explanations to thousands of textbook problems written by our experts, many with advanced degrees!

Get Started

#### In Exercises 2340, find the indicated limit. 28. limt3(4t22t+1)

Applied Calculus for the Managerial, Life, and Social Sciences: A Brief Approach

#### Divide: 45.242.4

Elementary Technical Mathematics

#### For

Study Guide for Stewart's Multivariable Calculus, 8th

#### True or False: If f′(x) = g′(x), then f(x) = g(x).

Study Guide for Stewart's Single Variable Calculus: Early Transcendentals, 8th

#### Find each value of x. log5x=-2

College Algebra (MindTap Course List) 